On empirical challenges in forecasting market betas in crypto markets - Jan Šíla; Michael Mark; Ladislav Krištoufek (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This paper investigates the predictability of market betas for crypto assets. The market beta is the optimal weight of a short position in a simple two-asset portfolio hedging the market risk. Investors are therefore keen to forecast the market beta accurately. Estimating the market beta is a fundamental financial problem and we document pervasive empirical issues that arise in the emerging market of crypto assets. Although recent empirical results about US stocks suggest predictability of the future realized betas about 55%, predictability for the universe of crypto assets is at most 20%. Our results suggest that the crypto market betas are highly sensitive not only to the beta estimation method but also to the selection of the market index. Thus we also contribute to the discussion on the appropriate market representation.
Keywords: C21; C53; C58; G12; 330; Asset pricing; CAPM; Market Beta; Cryptocurrency